Review of the Urinary Schistosomiasis Control in Morocco (1960–2018) - Balahbib, A.; Amarir, F.; Bouhout, S.; Rhajaoui, M.; Adlaoui, E.; Sadak, A. (Interdisciplinary Perspectives on Infectious Diseases, 2020)
The purpose of this study is to describe the epidemiological profile and evolution of urinary schistosomiasis in Morocco, from the first confirmed case in 1960 until disease elimination, and control snails. During this period, 129,526 cases were recorded in Morocco. A majority of cases were reported in Agadir province (25%), Errachidia (18%), and Beni Mellal (13%). Other cases have been reported in the other provinces. Activities within the National Schistosomiasis Control Programme for more than three decades were focused in priori on screening in schools located in high-risk communities, treatment program, surveillance of snails in water bodies, and mollusciciding. Then, the goal of eliminating the transmission of schistosomiasis has been reached in 2004. Sixteen years later, no indigenous cases were detected in Morocco, and only 25 residual cases (resulting from bilharziasis previously treated) are detected, such as in Tata ( 40%), Errachidia (16%), and (12%) in Marrackesh. Similarly, recent national studies conducted on children and the snail reservoir hosts have indicated that no human and molluscs are currently infected with Schistosoma haematobium. Actually, timely investigation and management of imported cases has been implemented to prevent the reintroduction of the disease. The Ministry of Health is planning to implement final confirmatory surveys before requesting WHO to proceed with the formal verification process.